Comparison of E-Wallet, QRIS and Paylater Digital Payment Methods from a Sharia Perspective - Lailatul Berliana; Nasya Amelia Putri; Siti Nurhaliza; Helmi, Helmi; Umar Gibran Assidqi; Hawa Gazani (Penerbit Hellow Pustaka, 2025)
The development of financial technology has given rise to various digital payment instruments, including e-wallets, QRIS, and Paylater, which are increasingly popular among the public. This study aims to analyze these three payment methods from an Islamic perspective, by reviewing the contracts used and their compliance with Sharia principles. The study results indicate that e-wallets are essentially permissible because they function as a storage medium (wadi'ah contract) and a transaction tool supported by sale and purchase contracts and ijarah, as long as they are not used for transactions of prohibited goods/services. QRIS is also permissible because it only functions as a QR code-based transfer and payment facility, provided it is free from elements of usury, gharar, and maysir. Meanwhile, Paylater has generated controversy; some scholars permit it if the installment contract clearly states without additional interest, but in practice, it is often accompanied by interest and late fees, thus constituting prohibited usury. This study concludes that the use of e-wallets and QRIS is in line with Sharia principles, while the use of Paylater should be avoided or limited to avoid violating Islamic law.